My life - Clinton, Bill 1946- (Knopf, 2004)
President Bill Clinton's My life is the strikingly candid portrait of a global leader who decided early in life to devote his intellectual and political gifts, and his extraordinary capacity for hard work, to serving the public. This is his story.
Keywords: Clinton, Bill <1946-> - Familia; Clinton family; Clinton, Bill <1946->; Clinton, Bill <1946-> -- Family; Clinton, Bill -- 1946-; Presidenten; Presidentes - Estados Unidos - Biografías; Politik; Politics -- United States; Presidents -- United States -- Biography; Estados Unidos - Política y gobierno - 1993-2001; USA; United States -- Politics and government -- 1993-2001; Autobiografie